Evaluation of a competitive enzyme‐linked immunosorbent assay for measurements of soluble HLA‐G protein. Issue 2 (2nd May 2014) - Rasmussen, M.; Dahl, M.; Buus, S.; Djurisic, S.; Ohlsson, J.; Hviid, T. V. F.
Abstract The human leukocyte antigen (HLA) class Ib molecule, HLA‐G, has gained increased attention because of its assumed important role in immune regulation. The HLA‐G protein exists in several soluble isoforms. Most important are the actively secreted HLA‐G5 full‐length isoform generated by alternative splicing retaining intron 4 with a premature stop codon, and the cleavage of full‐length membrane‐bound HLA‐G1 from the cell surface, so‐called soluble HLA‐G1 (sHLA‐G1). A specific and sensitive immunoassay for measurements of soluble HLA‐G is mandatory for conceivable routine testing and research projects. We report a novel method, a competitive immunoassay, for measuring HLA‐G5/sHLA‐G1 in biological fluids. The sHLA‐G immunoassay is based upon a competitive enzyme‐linked immunosorbent assay (ELISA) principle. It includes a recombinant sHLA‐G1 protein in complex with β2‐microglobulin and a peptide as a standard, biotinylated recombinant sHLA‐G1 as an indicator, and the MEM‐G/9 anti‐HLA‐G monoclonal antibody (mAb) as the capture antibody. The specificity and sensitivity of the assay were evaluated. Testing with different recombinant HLA class I proteins and different anti‐HLA class I mAbs showed that the sHLA‐G immunoassay was highly specific. Optimal combinations of competitor sHLA‐G1 and capture mAb concentrations were determined. Two versions of the assay were tested. One with a relatively wide dynamic range from 3.1 to 100.0 ng/ml, and another more sensitive version ranging from 1.6 to 12.5 ng/ml. An intra‐assay coefficient of variation (CV) of 15.5% at 88 ng/ml and an inter‐assay CV of 23.1% at 39 ng/ml were determined. An assay based on the competitive sHLA‐G ELISA may be important for measurements of sHLA‐G proteins in several conditions: assisted reproduction, organ transplantation, cancer, and certain pregnancy complications, both in research studies and possibly in the future also for clinical routine use.